2021
DOI: 10.1177/07067437211004881
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress among Iranians during COVID-19 Pandemic; Stressors and Coping Mechanisms: A Mixed-methods Approach

Abstract: Objective: New coronavirus (COVID-19) pandemic socioeconomically affected the world. In this study, we measured the perceived stress in response to the COVID-19 pandemic among Iranians to determine the groups at both extremes of the spectrum followed by identifying the stressors and coping mechanisms. Methods: This study was a mixed-methods study. We distributed a web-based 10-item perceived stress scale (PSS-10), to measure perceived stress score (PSS), through social networks from March 12 to 23, 2020. Then,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…The results of the current study highlight that perceived stress in COVID-19 patients who were hospitalized in the ICU for at least 24 h is high. The study by Faghankhani et al (2022) in Iran indicated that over half of the study population had high stress levels, and those who were hospitalized experienced more stress compared to other individuals ( Faghankhani et al, 2022 ). Furthermore, in another study conducted in Tehran, Iran, perceived stress among hospitalized COVID-19 patients was reported to be moderate to high ( Zandifar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study highlight that perceived stress in COVID-19 patients who were hospitalized in the ICU for at least 24 h is high. The study by Faghankhani et al (2022) in Iran indicated that over half of the study population had high stress levels, and those who were hospitalized experienced more stress compared to other individuals ( Faghankhani et al, 2022 ). Furthermore, in another study conducted in Tehran, Iran, perceived stress among hospitalized COVID-19 patients was reported to be moderate to high ( Zandifar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…From the psychological contract theory's perspective, leaders of organisations are expected to fulfil certain obligations sufficiently (Restubog et al, 2013) to ensure increase in employees' innovative behaviour. However, the onset of COVID-19 resulted in negative effect on most organisations finances (Faghankhani et al, 2021). As a result, several managers had to make changes in certain things like the introduction of remote work.…”
Section: Discussionmentioning
confidence: 99%
“…When employees perceive there has been psychological contract breach, it makes them anxious, lose concentration and exhibit negative emotions (Difonzo, et al, 2020) all antecedents of stress (Panigrahi, 2016) explaining why Arunachalam (2021) posit that Psychological contract breach causes stress. Stress reflects a detectable reaction to any change, which activates and reflects in physical and mental reactions (Faghankhani et. al, 2021).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The psychological well-being of nursing students during the pandemic is an important part of their academic success and requires appropriate coping mechanisms to deal with the situation. Many studies have investigated the perceived stress and coping strategies among university students, but fewer studies have correlated the situation to the pandemic [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. The perceived stress among nursing students is high and affects their psychological well-being, so they need a high level of resilience and coping mechanisms [17].…”
Section: Introductionmentioning
confidence: 99%